Overlapping and distinct relationships between hedonic hunger, uncontrolled eating, food craving, and the obesogenic home food environment during and after a 12-month behavioral weight loss program. (1st June 2023) - Crane, Nicole T.; Butryn, Meghan L.; Gorin, Amy A.; Lowe, Michael R.; LaFata, Erica M.
Abstract: Hedonic hunger, reward-driven eating outside of biological need, is a newer construct in eating behavior research. During behavioral weight loss (BWL), greater improvements in hedonic hunger are associated with higher weight loss, but it remains unclear if hedonic hunger predicts weight loss independent of more well-established, similar constructs (uncontrolled eating and food craving). Research also is needed to understand how hedonic hunger interacts with contextual factors (e.g., obesogenic food environment) during weight loss. Adults ( N  = 283) in a 12-month randomized controlled trial of BWL were weighed at 0, 12, and 24 months, and completed questionnaires assessing hedonic hunger, food craving, uncontrolled eating, and the home food environment. All variables improved at 12 and 24 months. Decreases in hedonic hunger at 12 months were associated with higher concurrent weight loss, but not when accounting for improvements in craving and uncontrolled eating. At 24 months, reduction in craving was a stronger predictor of weight loss than hedonic hunger, but improvement in hedonic hunger was a stronger predictor of weight loss than change in uncontrolled eating. Changes to the obesogenic home food environment failed to predict weight loss, regardless of levels of hedonic hunger. This study adds novel information on the individual and contextual factors associated with short- and long-term weight control, which can help refine conceptual models and treatment strategies.